NSTITUTE OF JOINT WILL OF SPOUSES IN RUSSIA AND A NUMBER OF FOREIGN COUNTRIES - MALETINA K.A.; SOKOLOVA A.G. (Legal Bulletin)
The article discusses the concept of introducing a new legal institution for the joint will of spouses for the Russian civil legislation. The relevance of the topic is reflected in the problems existing both in theory and in practice, namely: the lack of a legal definition of the concept of «will» in Russian legislation; the problem of video recording of the procedure for making a joint will; the possibility of canceling a joint will by a surviving spouse. The analysis and comparison of the norms of foreign legislation of a number of countries (Ukraine, Germany, Azerbaijan, Colombia, England, etc.) is carried out within the framework of the institute under consideration. The purpose of this work is to study the norms of domestic legislation, theoretical foundations and law enforcement practice, which are aimed at forming the institution of joint will of spouses, as well as the analysis of foreign legislation to establish its impact on domestic norms. In order to achieve the above-mentioned goal, the following tasks were identified, namely: analysis of Russian legislation in order to identify problems in the regulation of the institution in question; analysis of the norms of foreign legislation regulating this institution; study of the influence of the norms of foreign civil legislation on the understanding and formal consolidation of the system of joint will of spouses in domestic law; analysis of gaps related to the legal regulation of the regime joint wills of spouses in the Civil Code of the Russian Federation. The methodology of this research includes private and general scientific research methods, namely abstraction, analysis, synthesis, deduction, induction, method of legal experiment, legal modeling, comparative legal method. In conclusion, proposals were made to improve the norms of civil legislation concerning such a legal institution as the joint will of spouses.